Analisis Kemacetan Dan Perkiraan Tingkat Pelayanan Jalan Pada Masa Mendatang (Studi Kasus Jalan Raya Sawangan Depok) - Rangga Apriliyanto; Tri Sudibyo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2018)
The road growth relatively smaller than traffic volume growth caused decreasing of the road service level. The purpose of the research were indentified performance existing geometry condition and traffic condition of Jalan Raya Sawangan as well as to formulate program to resolve traffic jam. Existing condition performance of Jalan Raya Sawangan on segment 1 as well as 2 were classified as F and E whereas the non-signal intersection performance of the road was F. The geometry improvement was chosed to resolve traffic jam so the service level for the next 15 years could be calassified as D. Improvement of intersection performance was conducted by changing non-signal intersection becomed signal and changing the signal intersection becomed interchange. Signal intersection was only able to receive traffic load for 10 years thus re-upgrading was required to match with the planned target by changing the intersection to interchange. Service level of interchange obtained level A because suitable with the requirement. Keywords: geometry condition, service level, traffic growth, traffic jam